PERANAN GURU DALAM MENANAMKAN PERILAKU DISIPLIN ANAK PADA USIA 5-6 TAHUN - Enjely, Aprilyany; Halida, Halida; Amalia, Annisa (Universitas Tanjungpura, 2025)
This research aims to describe the importance of the teacher's role in instilling disciplined behavior in children aged 5-6 years at Pelita Kasih Kindergarten in Sintang City. The research method used is descriptive with a qualitative research design. The subjects in this study include the Head of the Kindergarten and two class teachers. The data collection techniques used in this research are interviews, observations, and documentation. The data analysis conducted consists of 1. Data collection. 2. Data reduction. 3. Data display. 4. Conclusion drawing/verification. The techniques to verify data validity include source triangulation, technique triangulation, and time triangulation. The research results on the role of teachers in guiding early childhood show that teachers still lack in guiding and serving as models and role models for children, such as throwing trash in the proper place, arriving on time at school, wearing uniforms according to regulations, guiding children to pray before and after lessons, directing children to tidy up toys after use, and instructing children to line up neatly. The conclusion of this study is that the role of teachers as guides, motivators, models, and role models is crucial in assisting students in developing positive behavior, encouraging them to be disciplined, and improving the quality of education in schools.